Islamic Financial Literacy and the Shaping of Consumption Patterns Among Indonesian Muslim Students - Subhan, Muhamad; Delvianti, Sintia; Septianti, Andini (Share: Jurnal Ekonomi dan Keuangan Islam, 2025)
The rapid growth of the digital economy in Indonesia has increasingly exposed Muslim university students to consumerist ideologies that frequently conflict with the ethical foundations of Islamic finance. Despite the efforts of student organizations like the Forum Silaturahmi Studi Ekonomi Islam (FoSSEI) to promote Islamic financial literacy through education and experiential learning, many students continue to exhibit consumptive behaviors shaped by peer influence, digital culture, and low financial awareness. This study aims to examine the role of Islamic financial literacy and lifestyle in shaping the consumptive behavior of Muslim students, with a specific focus on FoSSEI members in West and Central Sumatra. Utilizing a quantitative approach, data were collected through a validated questionnaire from 210 students, with 206 valid responses analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results show that Islamic financial literacy affects consumption behavior both directly and indirectly through lifestyle. Furthermore, lifestyle significantly influences consumptive behavior and serves as a mediator that strengthens or weakens the effect of financial literacy. These findings reveal that knowledge alone is insufficient; instead, lifestyle serves as a crucial behavioral channel through which financial literacy manifests. Theoretically, the study contributes by integrating lifestyle as a key mechanism in Islamic financial behavior models. Practically, the findings suggest that financial education programs must go beyond knowledge transfer to include lifestyle transformation, fostering more ethical and sustainable consumption aligned with sharia principles. Recommendations are offered to educators, policymakers, and Islamic financial institutions for designing more holistic interventions. Abstrak Literasi Keuangan Syariah dan Pola Konsumsi Mahasiswa Muslim di Indonesia. Di tengah pesatnya pertumbuhan ekonomi digital, mahasiswa Muslim di Indonesia semakin terpapar gaya hidup konsumtif yang sering kali bertentangan dengan etika keuangan Islam. Meskipun beberapa organisasi, seperti Forum Silaturahmi Studi Ekonomi Islam (FoSSEI) telah berupaya meningkatkan literasi keuangan syariah melalui program edukasi dan pembelajaran berbasis pengalaman, masih banyak mahasiswa dengan pola konsumsi berlebihan akibat pengaruh tekanan sosial, budaya digital, dan rendahnya kesadaran finansial. Penelitian ini bertujuan untuk menganalisis peran literasi keuangan syariah dan gaya hidup dalam membentuk perilaku konsumtif mahasiswa Muslim, dengan fokus khusus pada anggota FoSSEI di Sumatera Barat dan Sumatera Tengah. Menggunakan pendekatan kuantitatif, studi ini mengumpulkan data-data penelitian dengan kuesioner yang terstandarisasi dari 210 mahasiswa, dengan 206 respons yang valid. Hasil analisis dengan metode Partial Least Squares - Structural Equation Modelling (PLS-SEM) menunjukkan bahwa literasi keuangan syariah berpengaruh terhadap perilaku konsumtif secara langsung dan tidak langsung melalui gaya hidup. Gaya hidup juga terbukti memiliki pengaruh signifikan dan menjadi mediator penting yang memperkuat atau melemahkan efek literasi keuangan. Temuan ini menegaskan bahwa pengetahuan saja tidak cukup; gaya hidup menjadi saluran perilaku yang penting dalam mengaktualisasikan literasi keuangan. Kontribusi teoretis studi ini adalah integrasi gaya hidup sebagai mekanisme utama dalam model perilaku keuangan syariah. Secara praktis, studi ini merekomendasikan agar program literasi keuangan syariah tidak hanya berfokus pada pengetahuan, tetapi juga transformasi gaya hidup untuk mendorong konsumsi yang lebih etis dan berkelanjutan sesuai prinsip syariah.